2004
DOI: 10.1007/s11172-005-0015-z
|View full text |Cite
|
Sign up to set email alerts
|

4-Dimethylaminochalcone as fluorescent probe: effect of the medium polarity on relaxation processes in the excited state

Abstract: Relaxation processes in a 4 dimethylaminochalcone molecule after excitation with a light pulse of duration 70 fs were studied. During 0.4-1 ps after excitation, an absorbance of an excited state S 1 with a maximum at ~460 nm is formed in both polar and nonpolar media. Subsequent relaxation processes depend on the polarity of the medium. In nonpolar hexane, the 4 dimethylaminochalcone molecule transits to the triplet state having an absorption maxi mum at 570 nm (lifetime longer than 600 ps) for 20 ps. In polar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 4 publications
2
10
0
Order By: Relevance
“…The well-fitted evolution associated difference spectra (EADSs) and concentrations of transient species are obtained (see Figure ), and all the obtained time constants in different solvents are listed in Table . In CHX, after photoexcitation, the molecule has a high probability of ISC into triplet state (τ 1 ) according to the nanosecond TA results and previous calculations, , and the second lifetime component (τ 2 ) for DEAMC in CHX is assigned to the relaxation of the T 1 state back to the ground state. In THF, we attribute the first component (τ 1 ) to vibrational cooling or average solvation time of the initially Franck–Condon (FC) state, which is reached to an equilibrium situation through intramolecular vibrational energy redistribution and energy dissipation to the solvent molecules.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…The well-fitted evolution associated difference spectra (EADSs) and concentrations of transient species are obtained (see Figure ), and all the obtained time constants in different solvents are listed in Table . In CHX, after photoexcitation, the molecule has a high probability of ISC into triplet state (τ 1 ) according to the nanosecond TA results and previous calculations, , and the second lifetime component (τ 2 ) for DEAMC in CHX is assigned to the relaxation of the T 1 state back to the ground state. In THF, we attribute the first component (τ 1 ) to vibrational cooling or average solvation time of the initially Franck–Condon (FC) state, which is reached to an equilibrium situation through intramolecular vibrational energy redistribution and energy dissipation to the solvent molecules.…”
Section: Resultsmentioning
confidence: 67%
“…Earlier studies have shown that DEAHC has no or weak green fluorescence in solution but is strongly emissive around 700 nm when in bulk crystals; DEAMC is dark in both crystalline form and nonpolar solution but emits brightly in polar solution. , To explore their crucial microscopic dynamic mechanism, in this work, solvent-dependent excited state dynamics of both DEAMC and DEAHC are extensively investigated by using steady state spectroscopy, femtosecond and nanosecond transient absorption spectroscopy. We found that dramatic solvation effect induces stabilization of ICT state, restricting efficient formation of triplet states, enhancing the fluorescence yield of DEAMC . ,, Moreover, the stronger solvation process in polar solvents can further facilitate efficient ESIPT reaction in DEAHC .…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…So, the calculations show that after the initial excitation of a DMAC molecule to the 1 (p, p*) state, an effective cascade of relaxation 1 (p, p*) -1 (n, p*) -3 (p, p*) can occur. This results in rapid (several picoseconds, according to our experimental estimates) 11 population of the triplet 3 (p, p*) state.…”
Section: The Nature and Properties Of Dmac Lower Excited Statesmentioning
confidence: 61%
“…10 Basic processes that define the probe's fluorescence occur in its excited states. 11 This means that in order to assess specific contributions of radiative and nonradiative processes to the molecule's relaxation path, we had to determine the nature of its lowest excited states. This task is traditionally solved with quantum chemistry methods.…”
Section: Introductionmentioning
confidence: 99%